ChemInform Abstract: Highly Enantioselective Synthesis of α‐Azido‐β‐hydroxy Methyl Ketones Catalyzed by a Cooperative Proline—Guanidinium Salt System. Issue 25 (24th June 2014) - Martinez‐Castaneda, Angel; Kedziora, Kinga; Lavandera, Ivan; Rodriguez‐Solla, Humberto; Concellon, Carmen; del Amo, Vicente
Abstract The first enantioselective synthesis of α‐azido‐β‐hydroxy ketones via direct intermolecular aldol reaction of azidoacetone and aromatic aldehydes is described.